Correction of Immune Disorders in Patients with Abdominal Sepsis - O. A. Dolina; L. O. Shkrob (Общая реаниматология)
Objective: to estimate the diagnostic value of cerebral oximetry during cardiosurgical operations and to elaborate principles of the prevention of postperfusion neurological dysfunction. Subjects and methods. Four hundred and sixty-one patients operated on under extracorporeal circulation (EC) were examined. Cerebral oxygenation (CO) was monitored in all the patients. Pre-, intra-, and postoperative data were analyzed. Results. Two groups of patients were identified: 1) 148 patients with a reduced CO of lower than 45% during EC and 2) 313 patients without reduced CO. Group 1 was found to have lower preoperative levels of hemoglobin and packed cell volume and baseline reduced bilateral CO, more frequent concomitant brachiocephalic artery (BCA) stenoses of more than 50%, more detectable dyscirculatory encephalopathy (DEP) in the history. Group differences were found in the level of hemoglobin and packed cell volume, oxygen delivery, and PaCO2 during EC and there was a relationship of the rate of CO reductions to the type of cardioplegia. There were also group differences in the magnitude of CO reduction versus the baseline levels. In the postoperative period, encephalopathy (EP) was manifested in 24 (16.3%) and 12 (3.8%) patients in Groups 1 and 2, respectively (p<0.05). Decreased CO during EC was noted in 66.7% of the patients with postoperative EP. Conclusion. It is expedient to monitor CO at surgery with EC. A less than 45% decrease in CO, as well as its more than 20% reduction of the outcome levels during EC is a reliable predictor for the development of postoperative EP. The patients with preoperative anemia, concomitant BCA stenoses of more than 50%, manifestations of DEP in the history, as well as those with a baseline decreased CO of less than 70% were referred to as a group at risk for postoperative EC. Significant hemodilution and hypocapnia should be avoided in these patients during EC and preference be also given to blood cardioplegia. Key words: extracorporeal circulation, cerebral oximetry, neurological dysfunction, cerebral oxygenation.